التعويض المدني عن الأضرار الجسدية الناشئة عن حوادث المركبات في التشريع العماني: دراسة مقارنة - الزين، أحمد محمد أحمد (جامعة الحسن الأول - كلية العلوم القانونية والاقتصادية والاجتماعية - مختبر البحث قانون الأعمال, 2023)
يهدف هذا البحث لدراسة موضوع التعويض المدني عن الأضرار الجسدية الناتجة عن حوادث المركبات، ومن هذا المنطلق يكتسب هذا الموضوع أهميته لكونه يتعرض إلى كيفية معالجة الأضرار الناتجة عن حوادث المركبات التي تزداد يوما بعد يوم وفق معايير تضمن جبر الأضرار التي يتعرض لها الأفراد في حوادث المركبات بعدالة وإنصاف. تم التعرض في المبحث الأول لموضوع دعوى التعويض وأطرافها، وأساس المسؤولية في دعوى التعويض التي ترتكز على ثلاثة عوامل هي الخطأ الذي وقع والضرر الذي حدث للمصاب وعلاقة السببية بين الفعل والضرر، وكذلك تم تناول سلطة محكمة الموضوع في تقدير التعويض في حالة عدم وجود أرش مقدر، إذ أن لها سلطة تقديرية في الحكم بالتعويض بشرط أن يستند ذلك على أسباب سائغة لها أصلها الثابت في الأوراق. أما المبحث الثاني فقد تعرض بالدراسة لكيفية تقدير الضرر إذا كانت الإصابة دون النفس- والتي تختلف باختلاف الإصابة ونوعها- أو في حالة الوفاة. في ختام البحث تم التوصل لعدد من النتائج من أهمها أن دعوى التعويض عن الضرر المترتب على الحادث تسقط بعد مرور سنتين من وقوع الحادث وهذا الأمر قد يضر بالمصاب ولا يمكنه من رفع الدعوى؛ لأن دعوى المطالبة بالتعويض تسبقها دعوى جزائية لمحاكمة المتهم ثم بعد ذلك ترفع الدعوى المدنية وقد تنقضي هذا الفترة قبل انقضاء الدعوى الجزائية، كما تم التوصل لعدد من التوصيات من أهمها بأن تبدأ فترة التقادم بعد انتهاء الدعوى الجزائية؛ حتى لا يسقط حق المضرور في المطالبة بالتعويض بانقضاء هذه الفترة. This research aims to study the subject of civil compensation for bodily damage resulting from vehicle accidents, and from this point of view this topic acquires its importance because it is exposed to how to address the damages resulting from Vehicle accidents that are increasing day by day according to standards that ensure reparation for the damages suffered by individuals in vehicle accidents with justice and fairness. In the first section, the subject of the compensation lawsuit and its parties was addressed, and the basis of responsibility in the compensation lawsuit, which is based on three factors: the error that occurred, the damage that occurred to the injured and the causal relationship between Act and damage, as well as addressing the subject authority of the Court of First Instance in estimating compensation in the absence of an estimated arch, as it has a discretionary power to rule on compensation, provided that this is based on permissible reasons that have their origin Fixed in the record . The second section has been exposed to the study of how to estimate the damage if the injury does not cause the death - which varies according to the injury and its type - or in the event of death. At the end of the research, a number of results were reached, the most important of which is that the lawsuit for compensation for the damage resulting from the accident is subject to two year ‘statute of limitation from the occurrence of the accident, and this matter may harm the injured person and does not enable him to file a lawsuit; Because the claim for compensation is preceded by a criminal lawsuit to try the accused, and then the civil lawsuit is filed, and this period may expire before the expiry of the criminal case, and a number of recommendations have been reached, the most important of which are that the limitation period begins after the end of the criminal case, so that the right of the injured party to claim compensation does not lapse by the expiry of this period.
Keywords: حوادث السيارات -- الأضرار الجسدية -- التعويضات المدنية -- القانون العماني